Dynamics of Coupled Structures, Volume 4 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Allen, Matt.; Mayes, Randall L.; Rixen, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Dynamics of Coupled Structures, Volume 4. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the fourth volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Experimental Dynamic Substructuring • Structural Coupling of Nonlinear Structures • Analytical/Numerical Modeling of Joints • Industrial Applications of Substructuring • Source Identifi cation & Transfer Path Analysis • Human Induced Vibrations • Damping & Friction.
1 Verification of Experimental Component Mode Synthesis in the Sierra Analysis Framework -- 2 Multi-DoF Interface Synchronization of Real-Time-Hybrid-Tests Using a Recursive-Least-Squares Adaption Law:A Numerical Evaluation -- 3 Controls Based Hybrid Sub-structuring Approach to Transfer Path Analysis -- 4 Force Identification Based on Subspace Identification Algorithms and Homotopy Method -- 5 Response DOF Selection for Mapping Experimental Normal Modes-2016 Update -- 6 Experimental Modal Substructuring with Nonlinear Modal Iwan Models to Capture Nonlinear Subcomponent Damping -- 7 A Modal Model to Simulate Typical Structural Dynamic Nonlinearity -- 8 Optimal Replacement of Coupling DoFs in Substructure Decoupling -- 9 State-Space Substructuring With Transmission Simulator -- 10 Applying the Transmission Simulator Techniques to the Ampair 600 Wind Turbine Testbed -- 11 Effect of Interface Substitute when Applying Frequency Based Substructuring to the Ampair600 Wind Turbine Rotor Assembly.-12 Improving Floor Vibration Performance Using Interstitial Columns -- 13 Probabilistic Model Updating of Controller Models for Groups of People in a Standing Position -- 14 Fundamental Frequency of Lightweight Cold-Formed Steel Floor Systems -- 15 Fundamental Studies of AVC with Actuator Dynamics -- 16 Mitigating Existing Floor Vibration Issues in a School Renovation -- 17 Vibration Serviceability Assessment of An In-service Pedestrian Bridge Under Human-Induced Excitations -- 18 Numerical and Experimental Studies on Scale Models of Lightweight Building Structures -- 19 A Wavelet-based Approach for Generating Individual Jumping Loads -- 20 A Numerical Round Robin for the Prediction of the Dynamics of Jointed Structures -- 21 A Method to Capture Macroslip at Bolted Interfaces -- 22 A Reduced Iwan Model That Includes Pinning for Bolted Joint Mechanics -- 23 Nonlinear Vibration Phenomena in Aero-engine Measurements -- 24 Instantaneous Frequency and Damping from Transient Ring-Down Data -- 25 Explicit Modelling of Microslip Behaviour in dry Friction Contact -- 26 Modal Testing Through Forced Sine Vibrations of a Timber Footbridge -- 27 Damping Characteristics of a Footbridge - Mysteries and Truths -- 28 A Critical Analysis of Simplified Procedures for Footbridges' Serviceability Assessment -- 29 Human-Induced Vibrations of Footbridges: The Effect of Vertical Human-Structure Interaction -- 30 Nonlinear Time-Varying Dynamic Analysis of a Multi-Mesh Spur Gear Train -- 31 Energy Dissipation of a System with Foam to Metal Interfaces -- 32 Nonlinear System Identification of Mechanical Interfaces Based on Wave Scattering -- 33 Studies of a Geometrical Nonlinear Friction Damped System Using NNMs -- 34 Scale-Dependent Modeling of Joint Behavior -- 35 Robust Occupant Detection Through Step-Induced Floor Vibration By Incorporating Structural Characteristics -- Assessment of Large Error Time-Differences for Localization in a Plate Simulation -- 37 Assessment of Large Error Time-Differences for Localization in a Plate Simulation -- 37 Gender Classification Using Underfloor Accelerometry -- 38 Human-structure Interaction and Implications -- 39 Study of Human-Structure Dynamic Interactions -- 40 Characterisation of Transient Actions Induced by Spectators on Sport Stadia -- 41 Recent Issues on Stadium Monitoring and Serviceability: a Review -- 42 Characterising Randomness in Human Actions on Civil Engineering Structures -- 43 Optimal Restraint Conditions for the SID-IIs Dummy with Different Objective Functions -- 44 A Comparison of Common Model Updating Approaches -- 45 Experimental Coupling and Decoupling of Engineering Structures Using Frequency-based Substructuring -- 46 New FRF Based Methods for Substructure Decoupling -- 47 Experimental Determination of Frictional Interface Models -- 48 Effects of Experimental Methods on the Measurements of a Nonlinear Structure -- 49 Stress Waves Propagating Through Bolted Joints -- 50 A Comparison of Reduced Order Modeling Techniques Used in Dynamic Substructuring.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Solids; Machinery; Civil engineering; Multibody Systems and Mechanical Vibrations; Solid Mechanics; Machinery and Machine Elements; Civil Engineering